(untitled) (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: By analyzing the merit characteristics, practice value and humanistic value, this paper will promote the sport and promote national fitness. Methods: this article uses literature method, refers to electronic databases such as "China Knowledge Network" and "Wanfang", and searches relevant documents with the theme of "national fitness", "eight jin" and "health" respectively, which provides a theoretical basis for the research. Results: 1. Definition of Ba Duan Jin Ba Duan Jin is a set of traditional fitness methods with historical charm, which combines the Yin, Yang and five elements and meridians of traditional Chinese medicine. Since its publication, its practice and exploration have verified the many functions and functions of fitness Qigong Ba Duan Jin. Because it consists of eight actions, it is called "eight paragraph brocade". Since the Song Dynasty, it was gradually practiced into a sitting and vertical practice method, when people often nourish the mind and cultivate one’s morality. Ba Duan Jin is not limited by the site, with no need for equipment, but because of the advantages of simplicity and learning and obvious effect, it not only expands the masses to practice, but also lays a certain good foundation for the promotion of Ba Duan Jin. In addition, Badbrocade is also an embodiment of China’s traditional culture, which makes positive contributions to helping teenagers correctly understand the sports and fitness under traditional culture, and also has great significance to the development and carrying forward the traditional national sports culture. Characteristics and practice value of Ba Duan Jin Eight method composed of reserve, about eight commensurate action and potential, the middle of 8, respectively, two hands, left open bow like shooting carving, conditioning spleen and stomach must lift, five labor seven injuries look back, shake his head tail to fire, two hands climbing feet solid kidney waist, save fist anger and behind seven disease, each method has its unique significance, is a generation of health and practitioners to create knowledge wealth. Slow and coherent, easy to learn and remember. The first step is mainly to be soft and slow, circular and coherent as the practice goal. The practice process should not only maintain the focus of gravity on a level line, but also have a positive preventive effect on improving the balance and fall prevention ability of elderly Parkinson patients; and to determine the existing route of each action but meet the natural relaxation and bending state of each human joint. The eight method pays attention to the left and right matching, upper and down top, simple and easy to learn and easy to remember. The threshold is relatively easy to learn compared with a variety of Taijiquan. Looand tight combination, Dynamic and static combination. After understanding the law of action, the middle class mainly practice the static motivation and the static intention as the goal. In maintaining the correct body posture, physical and mental relaxed state, with the breathing to feel the ups and downs between the movement, conscious active control action and appropriate force, step by step, so that the movement and body cooperate more smooth and natural. The initiation, exhibition and collection of action and human breathing effectively stimulate the corresponding body parts, which has a significant effect on improving the exercise resistance and quality of life of patients with chronic obstructive pulmonary disease. The form of God, the unity of spirit. Higher order people are no longer confined to the presentation of action, actions pay more attention to God and shape, qi. ——, bred by physical activity combined with breathing, was proposed for the first time since the Jin Dynasty. Its movements, formula and breathing spitting requirements have all undergone several changes to. Modern scientific research shows that 50 percent of the diseases come from physiological and psychological disorders, and long-term practicing Duan Jin can not only relieve mental tension, relieve mental pressure, promote mental health, but also have good maintenance and promotion function, but also has a significant effect on the prevention and control of disease. Cultural value of Ba Duan. The gestation of Ba Duan Jin is the epitome of the culture of The Times. With the development of The Times, Ba Duan Jin’s merit method practice actions and requirements are also different. But whether it is vertical, sitting or south, north style are for practitioners to better practice and effective fitness, improve the physical quality. Now many colleges and universities have opened eight brocade courses, for sports class brought a new exercise mode at the same time, also to promote the promotion of the sport, in addition, through practical action, let teenagers feel the traditional culture "quiet" "harmony", the traditional culture into the body exercise, experience the traditional culture of profound and harmonious. Conclusion: Since ancient times, it has been a consensus of people to promote health, but scientific exercise methods are very important. The improper exercise methods may damage health and be counterproductive, which is also the reason why many people dare not go to exercise, worried about joint injury, strain and other consequences. However, for the traditional sport of Duan jin, not only the threshold is low, but also rarely too attention to the standard of action, the probability of injury is low, has a certain safety. Since August 8, 2009 was set as "National Fitness Day", more and more people pay attention to health exercise. As a traditional Chinese health method, Jin is set for health preservation. Therefore, it is necessary to promote Jin.